Local immunodefence and microbiocenosis at bowel diseases - V. T. Ivashkin; N. L. Denisov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study at chronic diseases of small and large intestine the concentration of immunoglobulins in intestinal contents, to estimate histological structure and severity of lymphoplasmacytic infiltration of lamina propria of proximal small intestine mucosa, to investigate a state of microbiocenosis of intestine.Material and methods. Overall 287 patients with chronic bowel diseases have been included in original study: 73 with irritable bowel syndrome (IBS), 55 – with irritable bowel syndrome with diarrhea (IBAD), 48 – with malabsorbtion syndrome (MS), 60 – with celiac disease (CelD) and 51 – with ulcerative colitis (UC). Concentration sIgA, IgA, IgG and IgM in intestinal contents was assessed in all patients. Histological investigations of mucosa of small intestine (MSI) have been carried out at 155 patients. The group of control consisted of 27 generally healthy people. Microbiocenosis of intestine was investigated at 37 generally healthy and at 177 patients with chronic bowel diseases (IBS – 36, IBDD – 36, MS – 35, CelD – 38 and UC – 32). Tests for concentration of immunoglobulins in small intestine contents, evaluation of morphology of proximal region of jejunum, and microbiologic study of contents of the small intestine and stool were executed according to standard procedures.Results. Atrophy of MSI, concentration of immunoglobulins in intestinal contents and disorders in microbiocenosis present in the different degree were the basic difference between groups of patients. At patients having UC, CelD and the MS, growing depression of secretion sIgA (from UC to CelD and MS) which severity coincided with depth of atrophy and density of infiltration of MSI by mononuclear cells was observed. Signs of bacterial overgrowth and change of microbial landscape of the intestine were present at all studied groups and intimately correlated with activity of function of immune elimination of the small intestine (sIgA) and grade of MSI atrophic changes. At IBS and IBSD changes of quantitative and qualitative parameters of intestinal microflora were mild or moderately severe. For these patients interrelation between activity of sIgA secretion at MSI both with degree of its bacterization by aerobic bacteria and with concentration in feces of lactobacilli (which was in inverse correlation to IgG) was characteristic. Diseases of the small intestine and UC were characterized by considerably more severe bacterization of proximal region of the small intestine in comparison to IBS. Significant decrease of function of immune elimination at the MS, CelD and UC was accompanied by overgrowth of opportunistic flora and depression of symbiotic microorganisms. Thus there were essentially new mutual relations between infectious and immune factors.Conclusion. Comparing to results of original study and numerous literature data it is possible to postulate that disorders in unite three-dimensional interaction system between epithelial lining of the gut, its microflora and local immune system underlie development of chronic intestinal disease.